Persentase komponen karkas ayam kampung super yang diberi tepung tongkol jagung fermentasi dengan level berbeda: Percentage of components super kampung chicken carcases served with fermented corn cob flour with different levels - Amiluddin Indi; Hamdan Has; Dina Hasria; Samsuddin; Rusli Badaruddin; Firman Nasiu (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2023)
This study aims to determine the carcass components of super free-range chicken on fermented corn cobs with different levels. This research was carried out in the laboratory of the Poultry Livestock Unit, Faculty of Animal Husbandry, University of Halu Oleo Kendari. This study used 64 super free-range chickens using a Completely Randomized Design (CRD) with 4 treatments, namely P0 (feed without fermented corn cobs) P1 (feed containing 2% fermented corn cobs) P2 (feed containing 4% fermented corn cobs) P3 (feed containing 4% fermented corn cobs) feed containing 6% fermented corn cobs) and 4 replications. The variables observed were slaughter weight, carcass percentage, carcass components, and abdominal fat. The data obtained were tabulated and analysed using analysis of variance. The use of fermented corn cobs in feed with a level of 2-6% does not significant effect (P>0.05) on slaughter weight, percentage of carcass, but significant effect (P<0,05) on abdominal fat of super native chicken.